Cost analysis of treating incomplete miscarriage with dilatation and curettage in Universiti Kebangsaan Malaysia Medical Centre in 2010 - A M Rizal,; I Aniza,; A B Jannatul Madihah,; A R Ahmad Fareed,; M S Natrah, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Background : Miscarriage is a common problem in pregnancy which can occur during early, mid or late pregnancy. Incomplete miscarriage can be treated expectantly, medically or surgically. The most preferred method used in UKMMC is using sharp curettage. Methodology : This study is conducted in the UKMMC from 1st January 2010 to 30th March 2010. The purpose of this study is to analyze the cost of treating incomplete miscarriage using metal sharp curettage from the provider’s perspective per patient-day. Result : A total of 17 samples were eligible for analysis from 46 patients who fulfilled the inclusion and exclusion criteria. The cost is derived from cost calculation on capital and recurrent costs. Results showed that the average cost for treating incomplete miscarriage using sharp curettage per day is RM252.56. Recurrent costs contributed 83.3% of the total treatment with overhead cost was the biggest percentage (51.6%). Discussion The treatment cost for incomplete miscarriage using sharp curettage is found to be higher as compared to medical approach according to literatures. The higher cost of surgical approach was mainly attributed to the recurrent cost which is included in the calculation. Conclusion : Effective usage of the operation theatre and all resources should be managed and utilized well in order to achieve optimum outcome.